The Role of Fur in the Transcriptional and Iron Homeostatic Response of Enterococcus faecalis - Latorre, Mauricio; Quenti, Daniela; Travisany, Dante; Singh, Kavindra V.; Murray, Barbara E.; Maass, Alejandro; Cambiazo, Verónica (Frontiers in Microbiology, 2018)
The Ferric Uptake Regulator (Fur) plays a major role in controlling the expression of iron homeostasis genes in bacterial organisms. In this work, we fully characterized the capacity of Fur to reconfigure the global transcriptional network and influence iron homeostasis in Enterococcus faecalis. The characterization of the Fur regulon from E. faecalis indicated that this protein (Fur) regulated the expression of genes involved in iron uptake systems, conferring to the system a high level of efficiency and specificity to respond under different iron exposure conditions. An RNAseq assay coupled with a systems biology approach allowed us to identify the first global transcriptional network activated by different iron treatments (excess and limited), with and without the presence of Fur. The results showed that changes in iron availability activated a complex network of transcriptional factors in E. faecalis, among them global regulators such as LysR, ArgR, GalRS, and local regulators, LexA and CopY, which were also stimulated by copper and zinc treatments. The deletion of Fur impacted the expression of genes encoding for ABC transporters, energy production and [Fe-S] proteins, which optimized detoxification and iron uptake under iron excess and limitation, respectively. Finally, considering the close relationship between iron homeostasis and pathogenesis, our data showed that the absence of Fur increased the internal concentration of iron in the bacterium and also affected its ability to produce biofilm. These results open new alternatives in the field of infection mechanisms of E. faecalis.